La sobreprotección de los padres de familia y su afectación en el desarrollo de la autonomía de las niñas y niños de primer grado de educación general básica del centro educativo Mercedes Quinde Burneo, cantón Catamayo, provincia de Loja, período 2012-2013. Propuesta alternativa - Pérez Dávila, María de los Ángeles (2015)
The investigation has for study object the sobreprotección of the family parents and its affectation in the development of the autonomy of the girls and children of first grade of Basic General Education of the Educational Center Mercedes Quinde Burneo, Canton Catamayo, County of Loja, and Period 2012-2013, did the investigation problem think about as the Sobreprotección of the family parents affects the development of the autonomy of the girls and children of first grade of basic general education of the educational center Mercedes Quinde Burneo Of what way, canton Catamayo, county of Loja, and period 2012-2013.?. The general objective of the investigation was to analyze the sobreprotección of the family parents in the affectation of the autonomy of the girls and children of the Educational Center Mercedes Quinde Burneo of the Canton Catamayo, period 2012- 2013, the methodology to carry out the investigation understood the deductive descriptive and hypothetical methods; the techniques that were used for the field investigation were the bibliographical one, the observation and the survey, the conclusions of more significatividad at the end of the investigation were: The sobreprotección of the parents to the children and five year-old girls, they determine situations of fear, distrust, edginess, suffering, cry, high sense of the ridicule and fear before the difficulties. The boy's dependence for effects of the sobreprotección has expressions in the school environment through intense cry especially in the first days of secularization, difficulties in the development of the language, he/she hopes the parents make him the educational tasks and it is always claiming attention and affection